The effect of covid-19 on airline sector in Algeria - Messamah , Imene (مجلة العلوم الاجتماعية والانسانية, 2022)
Covid-19 has negatively affected all sectors of the global economy, notably the airline sector due to travel restrictions and flight suspension worldwide. By examining documents and reports about the current situation of the sector around the world and in Algeria (the national company “Air Algérie”), this research seeks to understand the effects of the virus on the airline industry in Algeria. The results show that the company is facing huge challenges after the loss of 320 million dollars during covid, and suggests a re-evaluation of the company’s human resource and marketing management systems to survive this financial crisis.